2020
DOI: 10.26686/wgtn.12831857
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dietary sugars and body weight: Systematic review and meta-analyses of randomised controlled trials and cohort studies

Abstract: Objective: To summarise evidence on the association between intake of dietary sugars and body weight in adults and children. Design: Systematic review and meta-analysis of randomised controlled trials and prospective cohort studies. Data sources: OVID Medline, Embase, PubMed, Cumulative Index to Nursing and Allied Health Literature, Scopus, and Web of Science (up to December 2011). Review methods: Eligible studies reported the intake of total sugars, intake of a component of total sugars, or intake of sugar co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
144
0
17

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(161 citation statements)
references
References 15 publications
0
144
0
17
Order By: Relevance
“…Fibre also impacts on bowel health, with decreased risk of constipation (29) . In contrast, the consumption of free sugars (table sugar, fruit juice, honey, sugar-sweetened beverages or sugary snacks) could result in excess energy intake leading to overweight and obesity (32) .…”
Section: Role Of Carbohydrate In the Dietmentioning
confidence: 99%
“…Fibre also impacts on bowel health, with decreased risk of constipation (29) . In contrast, the consumption of free sugars (table sugar, fruit juice, honey, sugar-sweetened beverages or sugary snacks) could result in excess energy intake leading to overweight and obesity (32) .…”
Section: Role Of Carbohydrate In the Dietmentioning
confidence: 99%
“…The positive associations between consuming SSB and body weight gain are supported by dietary intervention studies in which subjects exhibited increased body weight when they consumed SSB with their usual ad libitum diet [ 14 ]. There are those who suggest this relationship is not unique to SSB and is simply the consequence of consuming any source of palatable energy in excess [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies demonstrate a positive association between consuming SSB and body weight gain [ 18 , 27 , 28 , 29 ••]. A meta-analysis of dietary intervention studies showed that increased sugar intake was associated with a weight increase (0.75 kg, 95% CI 0.30 to 1.19; P = 0.001) in adults consuming ad libitum diets [ 14 ]. This meta-analysis also showed that reduced intake of dietary sugars was associated with a decrease in body weight (0.80 kg, 95% confidence interval (CI) 0.39 to 1.21; P < 0.001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on legumes, one meta-analysis of ten RCT indicated that interventions to increase the intake of legumes were associated with decreased TC and LDL-C levels compared with a control group ( 91 ) , others reported reductions in C-reactive protein, SBP and FG ( 92 , 93 ) , but no effects on body weight ( 92 ) . Evidence from meta-analyses of intervention trials showed that higher consumption of sugar-sweetened beverages (SSB) leads to a considerable increase in body weight ( 94 , 95 ) .…”
Section: Current Evidence For Food-based Dietary Guidelinesmentioning
confidence: 99%